ANALISA KEBIJAKAN MITIGASI DAMPAK DAN STRATEGI PENURUNAN GAS RUMAH KACA DI PT XYZ MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCESS (AHP) - Djoko Suharyanto; Iman Basriman; Tatan Sukwika (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2022)
Environmental issues have now become a critical topic for the attention of countries around the world, especially efforts to prevent climate change by mitigating greenhouse impacts. There are six types of greenhouse gases, namely Carbon dioxide (CO2), Methane ( CH4 ), Nitrous oxide ( N2O ), Hydro perfluorocarbons ( HFC ), Perfluorocarbons ( CFCs ), Sulfur Hexafluoride ( SF6) this which naturally exists in the air (atmosphere). The gas layer causes infrared heat rays A to reflect sunlight, causing geothermal heat that reaches 13°C.    The earth's temperature will increase when the greenhouse gas layer gets bigger. Increased greenhouse gas (GHG) concentrations contribute to climate change by destroying stratospheric ozone and trapping excessive heat in the atmosphere. CO2 contributes 76.7% of total GHG emissions. Industrial activities are suspected to be one of the sources of co2 emission production. Research using the Analytic Hierarchy Process (AHP) method aims to analyze impact mitigation policies and GHG reduction strategies carried out by PT XYZ as one of the manufacturing industries committed to contributing to mitigating the impact of greenhouse gases. The research results obtained the Priority Policy on the operation of production machines at the Factory 1 location. The strategies carried out include replacing old machines that are no longer efficient with new machines that are more productive, and efficient in their electricity use, the use of high technology, and changing the layout or layout of machines that are more compact and grouped based on the type of product. From the analysis using the Analytical Hierarchy Process (AHP) method, it was concluded that the most priority greenhouse gas (GHG) impact mitigation policy was to reduce CO2 emissions based on the use of electrical energy by Reducing the use of electrical energy.